Haschavgiftningsprogrammet vid Maria Ungdom - Petrell, Birgitta; Nordberg, Arne (Socialmedicinsk tidskrift, 2007)
Vid Maria Ungdom pågår sedan ett par år en strukturerad öppenvårdsbehandling för ungdomar med mångårigt cannabismissbruk. I denna artikel beskrivs programmets inriktning, målgrupp, intagningsförfarande och arbetssätt. Behandlingen har en pedagogisk inriktning och pågår under sex veckor med tre sessioner per vecka. Programmet har utvärderats och ungdomarna har följts upp efter ett år med avseende på missbruk, hälsa och social funktion. Uppföljningen har presenterats i en FoU-rapport som sammanfattas nedan. At Maria Youth Centre a structured cognitive six-week treatment programme, including sessions three times a week, has been used since year 2000 to help adolescent chronic cannabis users. The main focus is on helping them stop using cannabis and to redirect their cognitive patterns and regain intellectual control. After completion of the six-week programme, the patients are advised to take part in support sessions once a week for six weeks. The treatment programme has been evaluated and the adolescents have been follow-up after one year concerning drugs, health and social functions. Fifty adolescent with at least six months daily use, completed the programme between year 2000 and 2004. After one year 67 per cent were drug free and they had a stronger sense of coherence (SOC, Antonovsky) and their psychiatric status (Symptomchecklist-90) were improved.